Th1, Th2, and Th17 cytokines in systemic lupus erythematosus - Farhana Muhammad Yusoff; Kah Keng Wong; Norhanani Mohd Redzwan (Autoimmunity, 2020)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the breakdown of immune tolerance leading to excessive inflammation and tissue damage. Imbalance in the levels of cytokines represents one of the multifactorial causes of SLE pathogenesis and it contributes to disease severity. Deregulated levels of T helper type 1 (Th1), type 2 (Th2), and type 17 (Th17) cytokines have been associated with autoimmune inflammation. Growing evidence has shown deregulated levels of Th1, Th2, and Th17 cytokines in SLE patients compared to healthy controls associated with disease activity and severity. In this review, we describe and discuss the levels of Th1, Th2, and Th17 cytokines in SLE patients, and clinical trials involving Th1, Th2, and Th17 cytokines in SLE patients. In particular, with the exception of IL-2, IL-4, and TGF-β1, the levels of Th1, Th2, and Th17 cytokines are increased in SLE patients associated with disease severity. Current phase II or III studies involve therapeutic antibodies targeting IFN-α and type I IFN receptor, while low-dose IL-2 therapy is assessed in phase II clinical trials.